Association between serum iron and liver transaminases based on a large adult women population - Andong He; Zhuoping Zhou; Lili Huang; Ka Cheuk Yip; Jing Chen; Ruiling Yan; Ruiman Li (BMC, 2023)
Abstract Background Studies are being focused on the potential roles of iron in various diseases, but remain unclear for the association between serum iron and liver injury, especially in adult women. Methods Based on the National Health and Nutrition Examination Survey, we investigated the relationship between serum iron and alanine aminotransferase (ALT) and aspartate aminotransferase (AST) among 19,185 adult women. Results Using weighted multivariate regression analyses, subgroup analyses, and threshold effect analyses, we found that serum iron was independently and positively correlated with ALT and AST. These associations differed in various age or race. Additionally, we found turning points in the curves of the relationship between serum iron and ALT in all women and the non-pregnant women. Using sensitivity analyses, we further found that the associations between serum iron and the liver transaminases remained positive in the non-pregnant women after adjusting for various covariates, but not in pregnant women. Besides, the positive associations between them kept present after excluding the women with high blood pressure, diabetes, and chronic kidney disease. Conclusion The present study indicated a positive association between serum iron and liver transaminases, indicating that serum iron may be a potential biomarker of liver function.